Neurocognitive health of older adults experiencing homelessness in Oakland, California - Mullady, Sandeepa Satya-Sriram; Castellanos, Stacy; Lopez, Lucia; Aguirre, Gloria; Weeks, John; King, Stephen; Valle, Karen; Goode, Collette; Tsoy, Elena; Possin, Katherine; Miller, Bruce; Kushel, Margot; et al. (Frontiers in Neurology, 2022)
Background and objectives The homeless population in the US is aging. Cognitive impairment is prevalent in this population, yet little is known about the neurologic etiologies of such impairment. Addressing this gap in knowledge is important because homeless older adults with cognitive impairment due to neurodegenerative disease may need lifelong tailored support to obtain and maintain housing. In this study, we characterized the neurocognitive health of a sample of adults who experienced homelessness for the first time after age 50 using gold standard behavioral neurology examination practices. Methods We conducted a descriptive cross-sectional study of older adults who first experienced homelessness after age 50. We recruited our sample purposively from an ongoing longitudinal cohort study of adults who were aged 50 and over and homeless when they entered the cohort. For this sub study, we enrolled a convenience sample from those who reported their first episode of homelessness after age 50. We did not exclude individuals based on history of substance use. Neurologists conducted a structured neurocognitive history intake, neurological examination, neuropsychological evaluation, and functional assessment between November 2020 and February 2021. We screened all participants for neurocognitive disorders using gold standard clinical research diagnostic criteria. Results We evaluated 25 participants, most were men (76%) and Black (84%), with a median age of 61 years. The most common neurocognitive complaints included deficits in recent episodic memory (n = 15, 60%), executive functions (n = 13, 52%), and behavior/mood, with apathy being the most common complaint (n = 20, 80%). Neuropsychological testing revealed a high prevalence of socioemotional deficits (n = 20, 80%). Common neurological examination deficits included difficulties with coordination, such as impaired Luria task (n = 16, 64%), signs of distal peripheral neuropathy (n = 8, 32%), anosmia/hyposmia (n = 4, 21%), and signs of mild Parkinsonism (n = 5, 20%). The most common diagnoses were MCI (n = 7, 28%), bvFTD (n = 4, 16%), AD (n = 4, 16%), and DLB (n = 2, 8%). Discussion Our findings suggest that neurocognitive concerns and examination deficits are common among older homeless adults. Specific neurocognitive disorders may be overrepresented in this population, particularly frontotemporal disorders. Longitudinal studies involving brain biomarkers are needed to characterize the neurocognitive health of this vulnerable population more precisely.